Interpersonal Meaning in President Prabowo Subianto's National Cooperative Day Speech: A Mood System Analysis - M. Asril Marpaung (Journal Of Global Research Publications, 2026)
This study examines the realization of interpersonal meaning through the Mood system in President Prabowo Subianto's speech delivered during the 2026 National Cooperative Day commemoration. Drawing on the interpersonal metafunction within Systemic Functional Linguistics, the study employed a qualitative SFL-based analysis supported by descriptive frequency counts. The official speech transcript was cross-checked against the corresponding video recording and systematically segmented into ranking clauses and independently functioning minor interpersonal units. Following a full segmentation and coding audit, the finalized corpus consisted of 680 interpersonal analytical units: 598 major clauses and 82 minor interpersonal units. Each major clause was analyzed in terms of its interpersonal grammatical structure and classified as declarative, imperative, or interrogative, while the minor interpersonal units were coded separately according to their interactional functions. The analysis also considered the grammatical characteristics of Indonesian and did not impose an English-type tense-based Finite on clauses without an overt interpersonal realization. The findings show that declarative Mood was dominant, occurring 524 times or 77.06% of all analytical units. Minor interpersonal units occurred 82 times (12.06%), followed by 41 imperative clauses (6.03%) and 33 interrogative clauses (4.85%). The predominance of declarative Mood indicates that the speech was primarily organized through the giving of information, positioning the President as the principal provider of propositions and the audience mainly as information recipients. Minor interpersonal units maintained ceremonial and interactional contact, while imperative clauses directed actions and responses. Interrogative clauses created temporary opportunities for confirmation, reflection, and audience involvement. Overall, interpersonal meaning in the speech was realized through a predominantly speaker-led but interactionally varied configuration of grammatical and interactional resources. The study contributes an audited full-speech account of spontaneous Indonesian presidential discourse, with explicit clause-segmentation criteria, an Indonesian-sensitive treatment of Finite, and a distinction between major Mood types and minor interpersonal units.